Development of the uno chemical card game as a learning medium on the chemical bonding material for high school student - Lilis Dahlianis; Iswendi Iswendi (Jurnal Pijar Mipa, 2023)
This study aims to develop chemical uno cards as learning media in class X senior high school in chemical bonding materials that are valid and practical. This type of research is development research using the Plomp model. This research has three stages, namely (1) preliminary research, (2) prototyping stage, and (3) assessment phase. The subjects of this research consist of 5 chemistry lecturers at the Faculty of Mathematics and Science, Padang State University, two chemistry teachers, and 12 students at SMA N 13 Padang for the 2021/2022 academic year. The research instruments used were self-evaluation sheets, one-to-one evaluation interview sheets, content validity questionnaires, construct media, and practicality questionnaires. Data analysis for validity uses Aiken's V formula, and practicality uses the percentage formula. The research results obtained a V value for material validation of 0.92 and media validation of 0.92, which are included in the valid category. The media practicality was obtained from the teacher's response of 96.8% and 94.4% of the students included in the very practical category.